Práticas de enfermagem e a autonomia profissional na atenção primária à saúde - SILVA, Sâmia Amélia Mendes (2022)
The Primary Health Care is proposed to promote amplified access and resolution of most prevalent problems in population. In vulnerable regions the nurses could take more functions with autonomy, in the public health programs stablished by the Ministry of Health, besides of contributing for the reduction of mortality in remote areas and with lack of service. Objective: Analyzing the nursing practices and the professional autonomy lived by the nurses that act in the Primary Health Care in a city in baixada maranhense (countryside). It is about a study with qualitative approach that was part of a macro-project of national coverage called “Nursing practices in the Primary Health Care (PHC) context: national study of mixed methods.” It was used as instrument of data collecting the half structured interview, done with 15 nurses that act in Family Health teams in Pinheiro, Maranhão. The thematic analysis and data interpretation were relied on the technique of content analysis of Bardin (2011) and and software NVIVO® version12. It was used as theoretical-methodological referential the process of working in health on Merhy’s perspective. From the 15 participants of the research 93,3% were woman and 6,6% were male, with age varying between 31 and 50 years old, 86,6% were self-declared “pardo” (brown skin) and 13,3% black, the average family income was 7 (seven) thousands reais, regarding to the marital status 40% were single, 33,3% married and 26,6% live in stable union. In relation to the professional profile 66,6% had post graduation latu sensu and 33,3% didn’t have or were studying, none of the nurses interviewed had post graduation stricto sensu, the time average of the acting in PHC was 4 years. Through the analysis of interviews emerged sense nucleus that were described in 4 empirical categories: Positive autonomy, Limited autonomy, Work process in PHC and Nursing practices in PHC and 17 subcategories that were described in 2 scientific paper. The results showed a practice normalized by the public health program of the Ministry of Health, the nurses related their limited autonomy to the work conditions, availability of supplies and absence of nursing protocols. The positive autonomy was related to the theoretical and practical knowledge, team management and Ministry of Health protocols. In the analysis made about the activities and work process of nurses, were highlighted too rigid schedules in punctual actions taking into consideration thematic months and activities determined by the management of the local PHC. The nurses understand the ESF as an environment propitious for the development of the professional autonomy, however, there still are many obstacles that must be overcome so they fully enjoy their autonomy such as factors related to the precariousness of the PHC, absence of material resources and equipments, low remuneration and the subordination to the doctor’s work. Severe structural and cyclical problems cause negative impact in SUS and in the population health.